2020
DOI: 10.1186/s13071-020-3904-y
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of Anopheles stephensi in eastern Ethiopia

Abstract: Background: The recent detection of the South Asian malaria vector Anopheles stephensi in Ethiopia and other regions in the Horn of Africa has raised concerns about its potential impact on malaria transmission. We report here the findings of a survey for this species in eastern Ethiopia using both morphological and molecular methods for species identification.Methods: Adult and larval/pupal collections were conducted at ten sites in eastern Ethiopia and Anopheles specimens were identified using standard morpho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 16 publications
5
125
1
Order By: Relevance
“…stephensi are also found in African populations), allowing it to avoid capture using typical African mosquito survey methods. Indeed, Balkew et al (17) comment that they captured few An. stephensi in their Centers for Disease Control and Prevention (CDC) light traps, and this is a method of survey often applied in Ethiopia.…”
Section: Significancementioning
confidence: 99%
“…stephensi are also found in African populations), allowing it to avoid capture using typical African mosquito survey methods. Indeed, Balkew et al (17) comment that they captured few An. stephensi in their Centers for Disease Control and Prevention (CDC) light traps, and this is a method of survey often applied in Ethiopia.…”
Section: Significancementioning
confidence: 99%
“…The current presence and the possible spread of An. stephensi to African countries poses a potential health risk since it is a malaria vector well adapted to urban centers and it could cause malaria outbreaks of unprecedented sizes (Balkew et al, 2019;Takken and Lindsay, 2019). Our model indicates that the breadth of temperature range for An.…”
Section: Discussionmentioning
confidence: 90%
“…stephensi is a native mosquito of Asia (Sinka et al, 2010), recent research has reported that An. stephensi mosquitoes are already present in Africa, for example in Djibouti (Faulde et al, 2014), Ethiopia (Balkew et al, 2019;Carter et al, 2018), Sudan, and probably in neighboring countries (Takken and Lindsay, 2019;World Health Organization, 2019). The current presence and the possible spread of An.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it spread into the Horn of Africa where it was reported in Djibouti city in 2013 [13] and Ethiopia in 2016 [14]. The recent emergence in the Republic of Sudan [15] and more widespread sites in Ethiopia [19] in 2019 suggests the species has the potential to become a widespread African malaria vector. Our data demonstrate that An.…”
Section: Discussionmentioning
confidence: 99%
“…Entomological surveys conducted in 2018 detected the occurrence of An. stephensi in Awash Sebat Kilo town [19].…”
Section: Methodsmentioning
confidence: 99%